Contribuição para o conhecimento da biologia de Pseudohypocera kerteszi (Enderlein, 1912), seu acasalamento e captura (Diptera, Phoridae). - Portugal-araújo, V. de (Acta Amazonica, 1977)
The aproachment of Pseudohypocera kerteszi (Enderlein, 1912) to the colonies of stingless bees, their mating behavior, and their recovery in traps are described. Copulation in the air in front of recently populated beehives and location of attempted oviposition by P. kerteszi is verified. A trap for capturing these phorids is described. In these traps the sex ratio varied from 2.3 females to 1 male to 2.8 females to 1 male.